Factors that Influence Fenofibrate Effects on Cancer Cells - A. Vlahopoulos, Spiros (Journal of Hematology and Oncology Research, 2014)
A narrative review summarizes how fenofibrate influences cancer cell metabolism and proliferation. It reviews PPAR‑α–dependent and independent mechanisms, context‑specific effects, and implications for repurposing studies.
Keywords: Fenofibrate; Cancer Cells; Cancer Cell Metabolism; Proliferation; Repurposing